Dietary niche partitioning between sympatric brown hares and rabbits. (18th April 2017) - Lush, L.; Ward, A. I.; Wheeler, P.
Abstract: Coexistence of ecologically similar species is sustained by niche partitioning, a fundamental element of which is diet. Overlapping of resource requirements between sympatric species can create interspecific competitive or facilitative effects on the foraging behaviour of herbivores. Brown hares ( Lepus europaeus ) and European rabbits ( Oryctolagus cuniculus ) are similar in size, morphology, feeding type and occupy the same habitats, but direct evidence of competition for resources between them is lacking. Both species are widespread and simultaneously pests and species of conservation concern in different parts of their range. We investigated dietary overlap of brown hares and European rabbits in pastures in relation to pasture management and hare and rabbit abundance. Grasses were the predominant component in both hare and rabbit diets with high overlap of plant species. Both rabbits and hares showed some selectivity for particular plants with evidence of consistent selection for Phleum spp. and relative avoidance of Poa spp. However, differences in the smaller components of hare and rabbit diet resulted in significant differences in diet overall. There was no evidence that higher relative density of one species led to dietary shifts but pasture management affected the diet of both species. Nutritional composition of diets of both species also differed between cattle and sheep pastures with higher fibre, ash and fat in the former. Our data provide no evidence of competitive exclusion between rabbits and hares on the basis of diet, but suggest that the effects of livestock on their respective diets may influence indirect competition in favour of rabbits over hares. Abstract : Coexistence of ecologically similar species is sustained by niche partitioning, a fundamental element of which is diet. Overlapping of resource requirements between sympatric species can create interspecific competitive or facilitative effects on the foraging behaviour of herbivores. We investigated dietary overlap of brown hares and European rabbits in pastures in relation to pasture management and hare and rabbit abundance. Both lagomorphs showed some selectivity for particular plants with evidence of consistent selection for Phleum spp. and relative avoidance of Poa spp. No evidence was found of competitive exclusion between rabbits and hares on the basis of diet, but our results suggest that the effects of livestock on their respective diets may influence indirect competition in favour of rabbits over hares.